Re-evaluating effects of water quality changes on soil hydraulic properties - Huber, David P., author; Butters, Greg, advisor; Garcia, Luis, advisor; Barbarick, Kenneth, committee member (Colorado State University. Libraries, 2011)
Elevated soil salinity has long been an agricultural concern, causing reductions in infiltration and crop yields, and in extreme cases loss of agricultural land. This study reexamines how salinity affects soil hydraulic properties in order to address deficiencies in prediction methods and management of salinity's impacts on soils. This research project explores the effects of both changing irrigation water electrical conductivity (EC) and sodium adsorption ratio (SAR) on soil hydraulic conductivity, K, and soil moisture retention, θ, over a range of soil water tensions. The Results show that a decrease in EC from 20 to 0.25 dS m-1, with SAR held constant at low to moderate levels, causes changes in K(θ) only after dropping below 1.5 dS m-1 for soils at this particular site. The initial K(θ) could not be recovered by increasing the EC to its original level, indicating that irreversible clay dispersion had taken place. Increasing SAR from approximately 4 to 25 with EC held at 0.5 dS m-1 caused slight reductions in K(θ). In contrast to the EC treatment, K(θ) partially recovered after the SAR was reduced to its initial condition. The mechanism for the SAR effect is clay swelling and is reversible with changing soil water chemistry. The results from both EC and SAR treatments are consistent with other research reports. However, in contrast to previous studies and of particular interest is the magnitude of change in K with changing EC or SAR and decreasing θ. Unlike current models that assume the decline in K due to solution chemistry is constant over the entire K(θ) range, equal to the change at Ksat, this study observes an exponential increase in the solution chemistry's effect on K with decreasing θ. These findings suggest that current models that ignore solution chemistry, or models that assume a constant K reduction for the entire K(θ) function, are over-estimating the drainage in these systems. Adoption of a more characteristic solution chemistry model, similar to the one presented here, could help better manage irrigation water quality, reduce salt accumulation, and improve crop yields.
Keywords: soil; Colorado; hydrology; hysteresis; modelling; salinity